Food Prices Volatility and Farmer’s Terms of Trades: Basis of Policy and Program Formulation for Farmers - Jun Rex Perez; Liana Louise F. Moreno; Karl P. Campos (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The economic support of many farmers in the Philippines is shaky, mainly due to the unstable prices of the agricultural products and livestock they deal in, along with the constant increase in the prices of basic necessities. The research investigated the link between food price volatility and Farmer’s Terms of Trade (FTT), which is a metric for measuring farmers’ purchasing power, for the period from 2018 to 2024. Six leading commodities, namely rice, copra, lakatan banana, pork, broiler chicken, and cattle, were studied. The volatility of food prices was assessed using Coefficient of Variation (CV), while FTT was computed through the use of Producer and Consumer Price Index data. The analysis unveiled that rice was the least fluctuating item and thus, it provided farmers with a more stable income source. Bananas came next with less variability. On the other hand, copra prices were the least stable, as reflected by the extremely high CV, indicating a very risky market. Among the animals, pork, being the most volatile, faced high prices and disease outbreaks. The FTT numbers showed severe poverty issues from 2018-2020, meaning farmers’ incomes had fallen behind their needs, hence they could not afford to live. The situation slightly improved from 2021 when a partial recovery was seen, but the values remained close enough to indicate a very weak improvement in buying power. The results imply that the combination of high price volatility and weak FTT means farmers ascend through the low-income tunnel, and their welfare gets worse.